PERAN GURU BIMBINGAN DAN KONSELING DALAM MENGATASI KESULITAN BELAJAR PESERTA DIDIK BERKEBUTUHAN KHUSUS PADA PENDIDIKAN INKLUSI DI SMK NEGERI 4 PADANG - Endrawati, Endrawati; Kasih, Fitria; Nita, Rahma Wira (Bimbingan dan Konseling, 2014)
This research motivated by presence of students special needs who have barriers learning . Learners  special needs not as fast as other students receive lessons. The purpose this study determine role of teacher in exposing counselor learning difficulties and  provision counseling services in overcoming learning difficulties . This study conducted with qualitative descriptive approach describes symptoms , facts and reality environment about the role of  teachers in overcoming learning difficulties BK learners special needs in inclusive education . As for  research informants are : counselor  and learners with special needs . Instrument used by writer in this study were interviews and observation techniques used in processing data through data reduction, data display conclutionThe results obtained are special needs students center and in front of the class room . Conduct interviews with parties such as parents , peers , teachers teach , students learn about difficulties and development, as well as direct observation and diagnostic tests for learners special needs, observe directly development learners with special needs .BK teachers role in overcoming learning difficulties of students  special needs in provision of services , namely : Inform teacher who taught for more attention to students special needs in teaching